The rocky road to the Great War : the evolution of trench warfare to 1914 - Murray, Nicholas, 1966- (Potomac Books, 2013)
Nicholas Murray's The Rocky Road to the Great War examines the evolution of field fortification theory and practice between 1877 and 1914. During this period field fortifications became increasingly important, and their construction evolved from primarily above to below ground. The reasons for these changes are crucial to explaining the landscape of World War I, yet they have remained largely unstudied. The transformation in field fortifications reflected not only the ongoing technological advances but also the changing priorities in the reasons for constructing them, such as preventing desert.